2007
DOI: 10.1086/516758
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the History of Selection during Homoploid Hybrid Speciation

Abstract: This study aims to identify selection pressures during the historical process of homoploid hybrid speciation in three Helianthus (sunflower) hybrid species. If selection against intrinsic genetic incompatibilities (fertility selection) or for important morphological/ecological traits (phenotypic selection) were important in hybrid speciation, we would expect this selection to have influenced the parentage of molecular markers or chromosomal segments in the hybrid species' genomes. To infer past selection, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 61 publications
1
37
1
Order By: Relevance
“…Several cases of fertile homoploid natural hybrid populations were previously reported within Centaurea (Fernández Casas and Susanna 1986) and in other Asteraceae genera, such as Senecio L. (López et al 2008) and Helianthus L. (Gross et al 2003), as well as in other plant families (Howarth and Baum 2005;Pan et al 2007;Wang et al 2008). Even if homoploid hybrid speciation has traditionally been considered a rare event, recent studies suggest this phenomenon may be more frequent than previously considered (Chapman and Burke 2007;Karrenberg et al 2007;Rieseberg and Willis 2007;Buerkle and Rieseberg 2008;Seehausen et al 2008). …”
Section: Persistence Of the Hybridmentioning
confidence: 85%
“…Several cases of fertile homoploid natural hybrid populations were previously reported within Centaurea (Fernández Casas and Susanna 1986) and in other Asteraceae genera, such as Senecio L. (López et al 2008) and Helianthus L. (Gross et al 2003), as well as in other plant families (Howarth and Baum 2005;Pan et al 2007;Wang et al 2008). Even if homoploid hybrid speciation has traditionally been considered a rare event, recent studies suggest this phenomenon may be more frequent than previously considered (Chapman and Burke 2007;Karrenberg et al 2007;Rieseberg and Willis 2007;Buerkle and Rieseberg 2008;Seehausen et al 2008). …”
Section: Persistence Of the Hybridmentioning
confidence: 85%
“…A majority of homoploid hybrid species described to date have a mosaic genome (mosaic genome hybrid speciation; Jiggins et al, 2008), where genomic differences are sorted in the hybrid genome through both fertility and ecological selection (Karrenberg et al, 2007). In the most well studied of these systems, chromosomal rearrangements have a substantial role in strong postzygotic isolation between several independently derived homoploid hybrid sunflower species and their progenitors (Rieseberg et al, 1995;Rieseberg, 2000;Lai et al, 2005), as was predicted in earlier verbal models of homoploid hybrid speciation (Grant, 1971).…”
Section: Introductionmentioning
confidence: 91%
“…Analysis of genome structure in three synthetic and three natural hybrid species of sunflower revealed massive karyotypic change over a handful of hybrid generations [31,32]. While some of the karyotypic differences arose through the sorting of chromosomal rearrangements that distinguish the parental species, most arose de novo.…”
Section: Genomic Alterations In Hybridsmentioning
confidence: 99%
“…The most detailed analysis of the evolutionary forces responsible for fixing favored combinations of parental alleles or chromosomal segments in hybrids focused on recombination in the homoploid hybrid sunflowers [31]. Analysis revealed that selection on ecological traits had slightly higher power than selection for fertility when predicting hybrid genomic composition, although both forms of selection were significant.…”
Section: Evolutionary Consequences Of Introgression and Hybrid Speciamentioning
confidence: 99%